THE COMPOSITION OF THE ADMINISTRATIVE OFFENCE AND THE PROBLEMS OF ITS QUALIFICATIONS - Zikina, Jelena (Administrative and Criminal Justice, 2021)
The administrative-legal science pays a great attention to the study of administrative offences’ qualification. When analyzing any part of an administrative offence, the issues of qualification always take the lead. This paper focuses on the most controversial and at the same time practically important issues. The composition of an administrative offence is a legal basis for the qualification of an administrative offence in accordance with a specific article of the law establishing administrative responsibility.The structure of an administrative offence is a combination of four elements: the object, the objective side, the subjective side and the subject, the presence of which is necessary and sufficient for the recognition of a socially harmful act as an administrative offence. These elements are called necessary because they must be present in any case when deciding whether to bring to administrative responsibility. In the absence of at least one of these elements, a person cannot be held administratively liable.In this paper, the composition of an administrative offence is considered as the basis for the qualification of administrative offences. In connection with the mentioned above, the problems’ study of administrative offences’ qualification, necessitates the further theoretical study of issues related to its concept, purpose, and implementation.